GENES ENCODING SYNTHESIS OF PHENAZINE-1-CARBOXYLIC ACID IN Pseudomonas batumici - V. V. Klochko; S. D. Zagorodnya; O. N Reva (Biotechnologia Acta, 2016)
The aim of this research was to elucidate the role of fenesin-1-carboxylic acid of Pseudomonas batumici and diversity of the genes encoding its synthesis in bacteria of the genus Pseudomonas. Phenazine-1-carboxylic acid in the concentration of 10 μg/ml stimulated the biofilm formation by batumin-producing strain. The presence of the corresponding gene in the genome of P. batumici was not successfully confirmed by PCR amplification with a set of primers designed for Pseudomonas. The complete genome sequencing of P. batumici has revealed a homologous gene that could encode synthesis of this compound. Comparative study of sequenced Pseudomonas genomes showed presence of at least two genetically diverse groups of phenаzine coding orthologous genes. These genes could have distributed among rhizobacteria by the horizontal gene transfer.